Electronic and hybrid vehicles - Tom denton; Hayley pells (New york : Routledge taylor & francis group, 2024)
Endorsed by the Institute of the Motor Industry, this full colour textbook introduces the subject for further education and undergraduate students, technicians, and drivers. This edition is extensively updated, especially regarding batteries, charging and the high voltage pathway, and with new case studies and illustrations. It covers the different types of hybrid and electric vehicle, costs and emissions, and the charging infrastructure, and then explains how the vehicles work, plus the maintenance and repair procedures. Includes index
Keywords: Electric vehicles